Exploring empathy and self-efficacy in communication skills among nursing students: A cross-sectional study at two universities in the MENA region - Fatma Refaat Ahmed; Samah A Shalaby (Elsevier, 2022)
Background: Empathy is an integrated multifaceted concept that has emotional, cognitive, moral, and behavioral aspects. Nurses' empathic attitudes convey a caring message to their patients and promote improved patient outcomes. A major challenge for student nurses is establishing a therapeutic nurse-patient relationship. This challenge should be reflected in nursing curricula. Aim: To explore empathy levels and identify factors contributing to empathy perception among nursing students at Sultan Qaboos University (SQU) and Alexandria University (AU). Design: This was a descriptive exploratory correlational study. Methods: Convenience sampling was used to recruit 500 nursing students from two public universities in Egypt and Oman. Data were collected with t a self-report three-part questionnaire that covered: 1) students' demographic and academic characteristics; 2) the Jefferson Scale of Empathy for Nursing Students, which measures empathy among nursing students; and 3) the Communication Skills Self-Efficacy Scale, which measures healthcare professionals' clinical communication skills self-efficacy. The present study relies mainly on Communication theory as a theoretical framework. Descriptive and analytical statistical methods were used to analyze the data. Results: Participating nursing students had moderate levels of empathy (AU: 92.80 ± 19.70; SQU: 84.29 ± 15.24). Communication self-efficacy, clinical score, academic level, and preference for the nursing profession were factors that significantly contributed to empathy levels (P = 0.000). Conclusion: Nursing students had moderate empathy levels. Use of continuous reflection and regular educational activities are recommended to improve students' empathic attitudes and caring behaviors.